Exploring inside the computer with 3D environment / Muhammad Zikri Mohamad - Mohamad, Muhammad Zikri (2016)
In this modern world, technology is important and now it has already becoming as platform for people to acquire knowledge and information. There is several method of learning such as discussion, exploring and study group. By using virtual reality approach, user can learn by using exploring. Senses of the body part are needed to make an interaction with the computer, and it also immerses the user into the virtual world. Computer component is very sensitive to the human hand because computer component has reputation for being finicky to troubleshoot. Thus, virtual reality method by using desktop based has become the solution to overcome those problems. This project develop using ADDIE methodology consisting analysis, design, develop, implement and evaluate. The methodology is suitable for this project. This project was evaluated by 10 student of first semester Computer Science student using effectiveness testing. In this project, two methods are used to test project effectiveness. The method are using book and learning application. Both are used the same questionnaire paper. Response was analyzed and the result indeed proven learning using application in 3D Environment have more advantage to the user.